Stationary and non-stationary method for solving system of linear equation - Ferdinan Rinaldo Tampubolon; Sinta Marito Siagian; Samaria Chrisna; Rischa Devita; Indah Nurhidayati (International Journal of Basic and Applied Science, 2023)
System of Linear Equation  where  is a non-singular and square matrix .  Method for solving System of Linear Equation consist of direct method and indirect method. Further indirect methods were divided into two, that is stationary and non-stationary. This research will conduct a comparative study of several indirect methods and direct methods in solving several cases of Linear equation systems. Some methods that will be compared in this research are jacobi, gauss-seidel, SOR, conjugate and biconjugate gradient. Testing several methods for some kind of matrix is useful to understand the characteristics of each method in solving different types of matrices. The result show that non-stationary such as conjugate and biconjugate has a less computation and faster to convergence compared to stationary method for several symmetric and non-symmetric matrices